Perspective of self-help groups, Panchayati Raj institution and adolescents on implementing COVID appropriate behavior in the community in rural settings - Alekhya, G.; Sahoo, Bimal Kumar; Taywade, Manish; Pal, Debkumar; Das, Kajal (International Journal of Research in Medical Sciences, 2022)
The vaccination drive in India brought cheers to the country's people, only to be eroded by the unpredictable twitch of the COVID-19 second wave. The best way to tackle the pandemic has been to adopt appropriate practices, thereby breaking the chain of transmission. The second wave in India has already created havoc both on the people and health system, questioning and challenging our capabilities to handle any heave of sudden cases, particularly in rural areas. Time has arrived to inflate our horizon by including groups of society close to the people, particularly in the rural community. Like the previous wave, COVID appropriate behavior was very much instrumental in slowing the pace. Adolescents’ self-help groups in coalition with Panchayat Raj Institutions (PRI) will be the main stand in the fight against the dreadful virus. Their main role is to translate the prevailing preventive measures into action among the very people they live around. Passing the right message through IEC/BCC to the right people will bring about dramatic changes in the attitude, belief, and exercise they do in their day-to-day life. PRIs members would utilize their powers to execute optimum administrative services. A decentralized approach involving these stakeholders will spearhead the fight against the pandemic. This trifold power shall bear the torchbearer in preventing the disastrous consequences of any upcoming wave, if any, in a holistic manner.